Peyzaj Tasarım Eğitiminde Bir Biçim Arama Yöntemi: Doğadan Esinlenme / A Form Creating Method in Landscape Design Education: Inspiration from Nature - Yılmaz, Serap; Düzenli, Tuğba; Çiğdem, Abdullah (Journal of History Culture and Art Research, 2018)
Abstract It is important how novice designers can produce shapes in the design-oriented parts where creativity and form creation is prior. Designers can abstract the t ideas in their minds by taking advantage of the forms, metrics, and relationships that exist in nature. For this reason, how designers can transform their ideas to forms has been analyzed by experienced designers in this research.The form of visual data obtained from the nature is obtained by the abstraction of the visual data and the addition of the designer’s own style instead of using the imitation of the individual. The shape of nature in the result of abstraction; there is a new meaning and form again. At the end of the study, the way of designing the system, as in the case of nature, will be guided by the designers in terms of measurement and direction. Thus, novice designers can improve their creativity. This formal quest: in landscape design, while the solution of the problem is both aesthetic and functional, Landscape architect candidates are encouraged to enrich visual memories by developing creative thinking and form creation. Öz Yaratıcılık ve biçim arayışının ön planda olduğu tasarım odaklı bölümlerde tasarımcı adaylarının nasıl biçim üretebileceği önemlidir. Tasarımcılar zihinlerindeki soyut fikirleri doğada var olan biçimlerden, ölçülerden ve ilişkilerden yararlanarak somut hale getirebilirler. Bu nedenle tasarımcıların fikirlerini nasıl biçime dönüştürebileceği bu araştırma kapsamında tecrübeli tasarımcılar tarafından analiz edilmiştir. Doğadan elde edilen görsel veriler birebir taklit edilerek kullanmanın yerine görsel verilerin soyutlanması ve tasarımcının kendi üslubunun da eklemesi ile biçim elde edilir. Soyutlama sonucunda doğadaki biçim; yeni bir anlam ve biçimle tekrar var olur. Çalışmanın sonunda yaratılan biçimin doğadaki gibi sistem tanımlaması için ölçü, yön açısından bir araya gelişinin irdelenmesi tasarımcılara yol gösterici olacaktır. Böylece tasarımcı adayları yaratıcılıklarını geliştirebilir. Bu biçimsel arayış: peyzaj tasarımında, problemin çözümünü hem estetik hem de fonksiyonel yaparken; peyzaj mimarı adaylarının yaratıcı düşünme ve biçim üretmelerini geliştirerek görsel hafızalarının zenginleşmesini sağlanmaktadır.